Effects of fou8/fry1 mutation on sulfur metabolism: is decreased internal sulfate the trigger of sulfate starvation response? - Lee, Bok Rye; Wirtz, Markus; Hell, Rüdiger (PLOS ONE, 2012)
The fou8 loss of function allele of adenosine bisphosphate phosphatase FIERY1 results in numerous phenotypes including the increased enzymatic oxygenation of fatty acids and increased jasmonate synthesis. Here we show that the mutation causes also profound alterations of sulfur metabolism. The fou8 mutants possess lower levels of sulfated secondary compounds, glucosinolates, and accumulate the desulfo-precursors similar to previously described mutants in adenosine 5′phosphosulfate kinase. Transcript levels of genes involved in sulfate assimilation differ in fou8 compared to wild type Col-0 plants and are similar to plants subjected to sulfate deficiency. Indeed, independent microarray analyses of various alleles of mutants in FIERY1 showed similar patterns of gene expression as in sulfate deficient plants. This was not caused by alterations in signalling, as the fou8 mutants contained significantly lower levels of sulfate and glutathione and, consequently, of total elemental sulfur. Analysis of mutants with altered levels of sulfate and glutathione confirmed the correlation of sulfate deficiency-like gene expression pattern with low internal sulfate but not low glutathione. The changes in sulfur metabolism in fou8 correlated with massive increases in 3′-phosphoadenosine 5′-phosphate levels. The analysis of fou8 thus revealed that sulfate starvation response is triggered by a decrease in internal sulfate as opposed to external sulfate availability and that the presence of desulfo-glucosinolates does not induce the glucosinolate synthesis network. However, as well as resolving these important questions on the regulation of sulfate assimilation in plants, fou8 has also opened an array of new questions on the links between jasmonate synthesis and sulfur metabolism.